Choroidal Thickness and microRNA146 in Lupus Nephritis Patients - Hassan Salah S (Dove Medical Press, 2020)
Shaymaa Hassan Salah,1 Hebatalla Samir Makled,1 Hany ElMekawey,1 Fatema T Elgengehy,2 Basma M Medhat,2 Noha M Abdel Baki,2 Dina Koptan3 1Ophthalmology Department, Kasr Alainy, Cairo University, Cairo, Egypt; 2Rheumatology and Rehabilitation, Kasr Alainy, Cairo University, Cairo, Egypt; 3Clinical Ophthalmology, Kasr Alainy, Cairo University, Cairo, EgyptCorrespondence: Shaymaa Hassan SalahKasr Alainy Hospital, 1 Saray Al-Manial, Cairo 11559, EgyptTel +201002229645Fax +20223636504Email Shaimaa.Sayed@kasralainy.edu.egPurpose: To evaluate the choroidal thickness (CT) in the macular area in patients with lupus nephritis and to compare the results with both non-nephritic patients and normal control. To assess the relation of CT to serum microRNA146, disease duration, activity index, and medications.Patients and Methods: Thirty-five SLE patients and thirty normal healthy controls were enrolled for this cross-sectional prospective study. All participants have undergone optical coherence tomography using RTVue OCT (Optovue Inc., Fremont, CA, USA). The scan used was the macular cross 6-mm line. We measured CT from the posterior edge of the retinal pigment epithelium (RPE) to the choroid-sclera junction at subfovea, and 750 μm both temporal and nasal to the fovea.Results: The mean central subfoveal CT in patients was 275.7 ± 41.0 μm (214– 374 μm), and the mean central subfoveal CT in the control group was 364.5± 23.0 μm (323– 411μm). There was a significant thinning at all three points in patients compared to the control group (p< 0.001, Mann–Whitney U-test). In the patients group, subfoveal choroid in non-nephritic subgroup showed significant thinning compared to nephritic subgroup (p=0.032, Mann–Whitney U-test). Drusen-like deposits (DLDs) were detected in 22.9% (8/35) of patients and none in control (p=.023). MiRNA146 showed a significant positive correlation with nephritic lupus patients (r=0.036, P=0.04).Conclusion: The choroidal thickness was significantly thicker among the nephritic lupus patients as compared to the non-nephritic subgroup. Both SLE patients’ subgroups are thinner than normal control. Subfoveal choroidal thickening can be considered a biomarker in nephritic lupus especially in conjunction with an increase in miRNA146a. All SLE patients are at risk of small Drusen-like deposits.Keywords: choroidal thinning, lupus nephritis, miRNA146a, SLEDI